The EARLY MARRIAGE IN ISLAMIC LAW: ADDRESSING SOCIAL AND ETHICAL CHALLENGES OF LEGISLATION - Millati, Najmatur Radhwa; Assidqi, Muhammad Raffa; Rosalia, Ami; Suresman, Edi (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2025)
Abstract Early marriage remains a prevalent phenomenon in various regions of Indonesia. This study aims to analyze the issue from the perspectives of Islamic law and national legislation, focusing on the underlying factors, as well as the social and health consequences and their relationship with legal and ethical values. The method utilized is a qualitative approach, which includes a literature review and the distribution of questionnaires to adolescent groups. The findings indicate that early marriage is influenced by several factors, such as economic pressure, family expectations, cultural values, and instances of marriage resulting from unplanned pregnancies, often referred to as "marriage by accident." The implications of this practice include mental unpreparedness, disruptions in the educational process, and an increased risk of divorce. Government laws, as stated in Law Number 16 of 2019, have set a minimum marriage age to safeguard children and adolescents, even though Islam does not explicitly forbid early marriage under specific situations. We hope that by doing this study, people will start to realize how dangerous child marriage is and how important it is to harmonize religious rules with governmental requirements. Keywords: Child marriage; Islamic law; social impact; contributing factors